Metode Mudarasah sebagai Upaya Peningkatan Menjaga Hafalan Al-Quran - Fikriyyah Qothrun Nadaa (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2021)
Mudarasah is peer listening of Al-Quran memorization to other people in turn and at the group perverse or several verses as settled by the teacher. This method is one of the efforts to always maintain memorization for a hafiz.